Towards automation of chemical process route selection based on data mining. Issue 1 (19th October 2016) - Jacob, P.-M.; Yamin, P.; Perez-Storey, C.; Hopgood, M.; Lapkin, A. A.
Abstract : A methodology for chemical routes development and evaluation on the basis of data-mining is presented. Abstract : A methodology for chemical routes development and evaluation on the basis of data-mining is presented. A section of the Reaxys database was converted into a network, which was used to plan hypothetical synthesis routes to convert a bio-waste feedstock, limonene, to a bulk intermediate, benzoic acid. The route evaluation considered process conditions and used multiple indicators, including exergy, E -factor, solvent score, reaction reliability and route redox efficiency, in a multi-criteria environmental sustainability evaluation. The proposed methodology is the first route evaluation based on data mining, explicitly using reaction conditions, and is amenable to full automation.